APPLYING THINK PAIR SHARE STRATEGY TO IMPROVE SPEAKING SKILL OF PHARMACY STUDENTS IN UNIVERSITY OF ADIWANGSA JAMBI - Silvia, Resi (LPPM Universitasdiwangsa Jambi, 2021)
Some problems are found in improving students’ speaking skill. Most of pharmacy students were unableto develop their ideas verbally. This research belongs to quasi experimental research with factorial 2x2.This study aims to find out the effect of Think Pair Share Strategy and students’ motivation toward theirspeaking skill of procedure text. This research was conducted in University of Adiwangsa Jambi.Pharmacy students are taken as the sample. Speaking test and questioners are used to collect the data. Inorder to test the significance between the groups, the independent samples t-test was used. The results ofthe research showed a significant difference between the students who were learned by applying ThinkPair Share strategy that was more successful and had higher motivation level. Based on the findings, itindicated that this strategy had significant effect on improving speaking skill and motivation.